Lassa Fever-associated Stigmatization among Staff and Students of the University of Benin, Nigeria - Stella Folajole Usifoh; Amienwanlen Eugene Odigie; Stephena Udinmande Ighedosa; Edwin Aihanuwa Uwagie-Ero; Isoken Tito Aighewi (Springer, 2019)
Lassa Fever (LF) remains a health burden in several endemic areas of Nigeria, and its toll remains unabated over several decades. Although most studies have focused on virological and clinical considerations, few studies have attempted to address the perceived psychosocial component of LF disease in Nigeria. Evaluation of stigmatization and discrimination faced by LF survivors is an important step in improving individual health and protecting public health. This study aimed to assess LF-associated stigmatization associated among staff and students of the University of Benin. Descriptive analyses of 600 consenting respondents (300 staff and 300 students) sampled using pretested questionnaires was conducted, and the Chi-square test was used to test for significant association between perceived LF stigmatization and predefined variables. LF was a potential cause of stigmatization in a higher proportion of student (n = 162, 57.9%) than staff (n = 112, 39.9%). LF-associated stigmatization among students was significantly associated with sex (p = 0.012) and poor knowledge (p = 0.013) of LF transmission and prevention. A greater tendency for stigmatization was observed among females than males. A comprehensive emergency response plan incorporating accurate knowledge dissemination about the disease may be a first step toward tackling perceived LF stigmatization.